EFEKTIVITAS KUNYIT (Curcuma domestica) SEBAGAI PEREDUKSI FORMALIN PADA TAHU - Zainal Berlian; Elfira Rosa Pane; Sri Hartati (Jurnal SainHealth, 2017)
The use of formalin increasingly widely circulated among sellers tahu, because nature tahu easily broken then the sellers know much use out using formalin. Turmeric has active compounds that issaponin. It can be used to minimize the presence of formaldehyde in tahu This study used tahu immersed in 5% formalin solution added a solution of turmeric. The research carried on in the Laboratory of the Polytechnic Palembang Health Nutrition Department. Determination of formaldehyde using a spectrophotometer test. The study used a completely randomized design (CRD) with a model of Factorial three factors, namely soaking treatment (60 minutes, 75 minutes, 90 minutes) giving a solution of Turmeric (0 %, 10 %, 15 %, 20 %) and storage factor (0, 24, 48, 72 hours). The parameters used are formaldehyde levels and organoleptic test. These results indicate that treatment of soaking time did not significantly affect the levels of formaldehyde in tahu that F count -0.022 smaller than F table 6.94. Treatment addition of turmeric solution concentration does not significantly affect the levels of formaldehyde at 0.864 tahu that F count is smaller than F table 3.16. The storage time treatment also did not significantly affect the levels of formaldehyde in tahu that F count -11.16 smaller than 2.73. However, the interaction between the immersion treatment, turmeric solution concentration and storage time significantly affect the levels of formaldehyde in the tahu, namely 282.16 F count larger than F table 1.75. And the results of organoleptic able to change the texture of aroma and color in tahu with decreasing levels of formaldehyde in tahu. In this study, formaldehyde levels lowest in 90 minutes soaking treatment, the concentration of 20 % deposit 72 hours .